2017
DOI: 10.5455/ajvs.277768
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Breed, Calving Season and Parity on Productive and Economic Indices of Dairy Cows

Abstract: Key words:. Although the similarity in total variable costs and total cost costs between the two breeds, Holstein cows had higher return parameters, than Brown Swiss cows. Cows that calved in the winter season had the highest total milk yield, daily milk yield, and corrected milk yield (305 milk yield), than other seasons. Breeding costs were higher for spring calvers. In spite of the higher labor, feed, variable and total costs, there is a superior increase profitability of winter calvers in comparison with o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
4
1
Order By: Relevance
“…Nicolas et al [ 48 ] narrated an agreeable result by reporting the direct proportionality of milk yield and parity number. Contrary to the current results, Mohamed et al [ 49 ] verified that parity numbers had no impact on production performances. In their report, scattered DMY with first, second, third, and fourth parity for exotic dairy cow were indicated 26.54 ± 0.14, 27.09 ± 0.15, 26.70 ± 0.21, and 25.55 ± 0.25, respectively, without a significance variation.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…Nicolas et al [ 48 ] narrated an agreeable result by reporting the direct proportionality of milk yield and parity number. Contrary to the current results, Mohamed et al [ 49 ] verified that parity numbers had no impact on production performances. In their report, scattered DMY with first, second, third, and fourth parity for exotic dairy cow were indicated 26.54 ± 0.14, 27.09 ± 0.15, 26.70 ± 0.21, and 25.55 ± 0.25, respectively, without a significance variation.…”
Section: Resultscontrasting
confidence: 99%
“…Liu et al [ 54 ] narrated, elevated temperature and humidity negatively affect feed intake, affecting the reproductive potential, which ultimately decreases milk production. Mohamed et al [ 49 ] conducted offensive results with non-significant variation between the winter (27.20 L) and summer (26.60 L) DMY of Holstein and Brown Swiss in Egypt. Baset et al [ 55 ] narrated an agreeable result on the effects of season on lactation milk yield.…”
Section: Resultsmentioning
confidence: 99%
“…These present results are in agreement with Sanad and Hassanane (2017) who found higher MY and shorter LP in winter and autumn compared to spring and summer for Friesian cows in Egypt. In the same trend, Abdel-Gader et al (2007) and Mohamed et al (2017) detected that TMY in winter was higher than in spring and summer. Additionally, Kamal El-den et al (2020) found also that season of calving has significant effect on TMY and LP, since cows calved in winter had significantly higher TMY (8369.01 kg) than those in other seasons.…”
Section: Resultsmentioning
confidence: 57%
“…Several studies showed a significant effect of season of calving on milk yield of cows (Chegini et al, 2015; Faid-Allah, 2015; Petrović et al, 2015;Mikó et al, 2016). Atallah et al (2015) showed that winter season and special sectors had the significant lead of milk production, also Mohamed et al (2017) concluded that, the winter calving and first three parties were more profitable for Holstein dairy producers. However, other studies stated that there were no significant effects of calving season on milk yield (Badri et al, 2011;Usman et al, 2012;Mikó et al, 2016).…”
Section: Introductionmentioning
confidence: 98%
“…Ahmed (2011),Atallah et al (2015) andMohamed et al (2017), who concluded that winter season had significantly higher profitability measures including milk return, total return and net return. Effect of parity order within production sector on some productive traits of Holstein-Friesian dairy cows.…”
mentioning
confidence: 99%